Doping MoS2 with Graphene Quantum Dots: Structural and Electrical Engineering towards Enhanced Electrochemical Hydrogen Evolution. (1st September 2016) - Guo, Jinxue; Zhu, Haifeng; Sun, Yanfang; Tang, Lin; Zhang, Xiao
Graphical abstract: Highlights: Hybrid of few-layered oxygen-incorporated MoS2 on graphene is prepared. Moderate oxygen-incorporation increases edge sites and conductivity. Tight coupling between hybrid nanosheets decreases charge-transfer impedance. Low onset overpotential, high current density, and small Tafel slope are achieved. Abstract: Nano-engineering is an effective strategy to achieve improved catalytic performance. A specific high-performance electrocatalyst of graphene quantum dots doped MoS2 nanosheets with defect-rich structures and improved electrical conductivity, referred as GQDs-MoS2, has been rationally designed and successfully developed through a facile hydrothermal method. XRD, SEM, TEM, and Raman techniques are employed to reveal the formation and the structural features. The doping of GQDs into MoS2 nanosheets plays the key role in enhancing the catalytic activity by creating abundant defect sites both in the edge plane and the basal plane, as well as enhancing the electrical conductivity. Endowed with this, the sample delivers remarkably improved catalytic properties for electrochemical hydrogen evolution reaction, including the large cathodic current (10 mA cm −2 at a small overpotential of 200 mV and 74 mA cm −2 at a small overpotential of 300 mV) and low onset potential (140 mV).